(untitled) (Palimpsesto, 2018)
Daniel Romero Holst’s La vida significativa de Felipe Erickson is an unclassifiable work that is not inbetweenthe novel and the short story but actually does not respond to any one of these genres. Besides, itpresents features, both in the realm of its plot and in the realm of the production of subjectivities, that arespecifically from Guayaquil, Ecuador, and at the same time fully global in their interchangeability. Usinga theoretical framework based on Glissant, this article isolates some of those features and inquiries intohow empty subjects who are in (de)composition are constructed in the narrative, in order to reflect on howsignificative La vida significativa really is.